Efektivitas Model Pembelajaran Problem Based Learning Dalam Meningkatkan Kemampuan Literasi Matematika Peserta Didik Sekolah Dasar - Harmika, Akbar Tsabet Al-Bahr; Ngurah Ayu Nyoman Murniati; Afina Farkhahani; Aryo Andri Nugroho (Jurnal Lensa Pendas, 2024)
The aim of this research is to determine the effectiveness of the problem based learning model in improving the mathematical literacy skills of elementary school students. This research is quantitative research using a pre-experimental design with one group pretest posttest type. The population of this study was class V students at SDN Sarirejo. Sampling was carried out using a saturated sampling technique. The sample for this research was all class V students at SDN Sarirejo, totaling 28 students. This research data collection technique uses pretest and posttest. The data analysis techniques used in processing the data are the normality test as a prerequisite test and the N-gain test to test the hypothesis. The results of this research show that the problem based learning model is effective in improving the mathematical literacy skills of elementary school students. The results of the N-gain test obtained a value of 0.64 which is in the criteria for increasing moderate mathematical literacy skills. So, learning should be centered on students and the teacher should only be a facilitator. In this way, students can further explore their abilities, including mathematical literacy abilities.